1990
DOI: 10.1161/01.hyp.16.4.436
|View full text |Cite
|
Sign up to set email alerts
|

A kallikrein-like enzyme in blood vessels of one-kidney, one clip hypertensive rats.

Abstract: Active and inactive kallikrein or a kallikrein-like enzyme are found in the aorta, vena cava, and tail artery and veins of the rat We studied the concentration of vascular ldninogenase in rats with one-kidney, one clip renovascular hypertension and in unilaterally nephrectomized normotensive rats. Six weeks after surgery, active and total vascular kininogenase activity (active plus trypsin-activated) was measured. Blood pressure was 212±4 mm Hg in the hypertensive rats (n=33) and 120±l mm Hg in the normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…Kininogenase activity found in the aorta of normotensive rats (active, 5.1±0.4 and inactive, 230±22 pg bradykinin/mg protein per minute, n=7) was lower compared with the levels reported by Nolly et al 3 but similar to that observed by our group in homogenates of human aorta. 9 Vascular kallikrein activity is decreased in the arteries of one-kidney, one clip hypertensive rats, 5 whereas the present study indicates that it is not altered by chronic administration of Ang II. Thus, reduced vascular kallikrein activity might be typical of volume-dependent hypertension.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Kininogenase activity found in the aorta of normotensive rats (active, 5.1±0.4 and inactive, 230±22 pg bradykinin/mg protein per minute, n=7) was lower compared with the levels reported by Nolly et al 3 but similar to that observed by our group in homogenates of human aorta. 9 Vascular kallikrein activity is decreased in the arteries of one-kidney, one clip hypertensive rats, 5 whereas the present study indicates that it is not altered by chronic administration of Ang II. Thus, reduced vascular kallikrein activity might be typical of volume-dependent hypertension.…”
Section: Discussioncontrasting
confidence: 73%
“…Oza et al 10 reported that rat vascular smooth muscle cells in culture release kinins, and vascular kininogenase activity is still present in rat vascular homogenates after endothelium removal by collagenase. 5 However, the finding that endothelial cells in culture are able to release bradykinin suggests that kallikrein may be located in both endothelial and smooth muscle cells. "…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinins are potent vasodilators, which acting as paracrine hormones, may be involved in the regulation of regional haemodynamics (Nolly et al, 1990;Saed et al, 1990;Wiemer et al, 1991;Gardiner et al, 1990;1992) and renal excretion of water and sodium (Willis et al, 1969;. Alteration of the function of locally formed kinins, leading to predominance of vasoconstrictor tone and retention of water and salt, may contribute to the pathogenesis of arterial hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…2 In fact, vascular endothelial cells (VECs), acting as sensors of intraluminal mechanical forces, release growth factors and vasoactive substances able to induce cell proliferation, migration, and death as well as matrix deposition. 2 The presence of a local kallikrein-kinin system in the vasculature is firmly established, [4][5][6] and evidence is now emerging regarding the possible participation of this system in vascular remodeling. Tissue kallikrein is a serine protease that cleaves low molecular weight kininogen to produce kinin peptides.…”
mentioning
confidence: 99%